Analisis Financial Distress dengan Model Z-Score, S-Score, dan X-Score - A’inun Hayat; Elok Heniwati; Rusliyawati, Rusliyawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research aims examine the potential for financial distress among issuers in the technology subsector—hardware & equipment—listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, using three classical prediction models: Altman Z-Score, Springate S-Score, and Zmijewski X-Score. This research adopts a quantitative descriptive approach with secondary data obtained from annual and quarterly financial statements, whose validity is ensured through official IDX sources and independent audits. The data were analyzed using descriptive statistics and the Kruskal–Wallis test to examine differences in classification results across models. The sample consists of seven companies with a total of 35 observations.The findings indicate that the Altman Z-Score detected one company (14.29%) in a financial distress condition and two companies (28.57%) in the grey area, while the Springate S-Score and Zmijewski X-Score classified all companies as financially healthy. The Kruskal–Wallis test produced an Asymp. Sig value < 0.05, confirming a statistically significant difference between the three models. These results suggest that the Altman model is more sensitive to fluctuations in leverage and working capital ratios, while the Springate and Zmijewski models tend to be more conservative and may under-detect early signals of financial distress.